Early Bajocian marine Gastropods from the Neuquén Basin, Argentina - Ferrari, Silvia Mariel (2015)
Nine gastropod species are reported from early Bajocian marine deposits at two localities in the Neuquén Basin, supplying the first detailed documentation of six gastropod families from the Middle Jurassic of Argentina at that time. The new gastropod species include Pleurotomaria bajociana sp. nov. (Pleurotomariidae); Cryptaulax weaveri sp. nov. and Rhabdocolpus(Infacerithium) excavatus sp. nov. (Procerithiidae); Anulifera sigmoidea sp. nov. (Protorculidae); Globularia andina sp. nov. (Ampullinidae); Eunerinea? neuqueniana sp. nov. (Eunerineidae) and Promathildia? spinosa sp. nov. (Gordenellidae). Leptomaria? leufuensis (Weaver) and Globularia klingamanni(Weaver) are also recorded from the same localities. Rhabdocolpus (Infacerithium) and Promathildia are mentioned here for the first time in the Argentinean Mesozoic, and Cryptaulax, Anulifera and Eunerinea extend their chronostratigraphical and paleogeographical distribution into the Bajocian of South America.